Retinal Capillary Nonperfusion on OCT-Angiography and Its Relationship to Kidney Function in Patients with Diabetes - Elysse S. Tom; Steven S. Saraf; FuPeng Wang; Qinqin Zhang; Gautam Vangipuram; Christine P. Limonte; Ian H. de Boer; Ruikang K. Wang; Kasra A. Rezaei (Journal of Ophthalmology)
Background. Diabetic retinopathy and kidney disease share underlying mechanisms of microvascular damage and are often comorbid in people with diabetes. We evaluated whether there is a relationship between retinal capillary perfusion as measured by swept-source optical coherence tomography angiography and estimated glomerular filtration rate (eGFR) and albuminuria in patients with diabetes and chronic kidney disease (CKD). Method. A cross-sectional pilot study was conducted at the University of Washington among a subset of participants with diabetes and CKD participating in a larger cohort study. Participants were excluded if they were known to have kidney disease from conditions other than diabetes. Ten participants (11 eyes) were included. Retinal nonperfusion (RNP) and vessel density (VD) were measured by swept-source optical coherence tomography angiography in 30° and 60° field of view (FOV) regions centered at the fovea. Correlations of RNP and VD with eGFR and albuminuria were analyzed. Results. Participants had a mean age of 72 years, hemoglobin A1c of 8.1%, eGFR of 45 mL/min/1.73 m2, and urine albumin-to-creatinine ratio of 162 mg/g. Mean (SD) RNP was 6.6% (4.2%) and 16.9% (7.7%) in 30° and 60° FOV regions, respectively. eGFR was negatively correlated to RNP in both the 30° and 60° FOV regions (R = −0.69, p=0.004, and R = −0.46, p=0.057, respectively), and correlations were stronger among a subset of 7 participants with evidence of diabetic retinopathy on exam and fundus photos. The estimated GFR was not significantly correlated with vessel density. Urine albumin-to-creatinine ratio was not significantly correlated with RNP or VD. Conclusions. Our proof-of-concept study showed that lower eGFR was significantly correlated with retinal nonperfusion in participants with diabetes and CKD. Advanced retinal imaging may enhance the noninvasive evaluation of kidney function in diabetes.